2022
DOI: 10.1093/mnras/stac2416
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances in the outskirts of nearby galaxy groups measured with joint Suzaku and Chandra observations

Abstract: We report results from deep Suzaku and mostly snapshot Chandra observations of four nearby galaxy groups: MKW4, Antlia, RXJ1159+5531, and ESO3060170. Their peak temperatures vary over 2–3 keV, making them the smallest systems with gas properties constrained to their viral radii. The average Fe abundance in the outskirts (R > 0.25R200) of their intragroup medium (IGrM) is ZFe = 0.309 ± 0.018 Z⊙ with χ2 = 14 for 12 degrees of freedom, which is remarkably uniform and strikingly similar to that of massive g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…The 𝛼/Fe ratios are found to be consistent with Solar abundances at their centers, but increase outside the cluster centers and reach 2× the Solar value. Interestingly, this latter measurement, with 𝛼/Fe profiles increasing with radius, is fully consistent with the prediction of the IllustrisTNG cosmological simulation (Sarkar et al 2022).…”
Section: Enrichment Process Of the Icmsupporting
confidence: 88%
See 3 more Smart Citations
“…The 𝛼/Fe ratios are found to be consistent with Solar abundances at their centers, but increase outside the cluster centers and reach 2× the Solar value. Interestingly, this latter measurement, with 𝛼/Fe profiles increasing with radius, is fully consistent with the prediction of the IllustrisTNG cosmological simulation (Sarkar et al 2022).…”
Section: Enrichment Process Of the Icmsupporting
confidence: 88%
“…The abundance ratios outside cluster cores have been observed with Suzaku for only a few clusters (Sarkar et al 2022;Simionescu et al 2015). However, unlike cluster centers, agreement on abundance ratios of cluster outskirts has not been reached.…”
Section: Enrichment Process Of the Icmmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, several studies reported the detection of the RS effect and demonstrated the importance of incorporating resonance scattering in modeling the X-ray spectra (Gilfanov et al 1987;Shigeyama 1998;Churazov et al 2004;Sanders & Fabian 2006;Nelson et al 2023). RS is crucial for the accurate determination of the abundances of heavy elements in the intracluster medium (Akimoto et al 2000;Sarkar et al 2022a), measurements of velocity fields and anisotropy of gas motion (Churazov et al 2010;Sarkar et al 2022bSarkar et al , 2023, and the polarization of bright X-ray emission lines in galaxy clusters and elliptical galaxies (Zhuravleva et al 2010). RS can be important for diagnostics of the density or ionization state using He-like ions, Fe L-shell ions, or the ratios of He-like to H-like ions (Schmelz et al 1992).…”
Section: Introductionmentioning
confidence: 99%